CHARACTER VALUES ANALYSIS OF MORNING PLEDGE TEXT AND ITS RELEVANCE IN THE DIGITAL ERA - Mahmudah, Nurul Laely; Fatkuroji, Fatkuroji (Universitas Negeri Padang, 2024)
This study aims to analyze the relevance of character values in the morning pledge text to the challenges faced by students in the digital era as well as explain how Al-Azhar 15 Semarang Islamic High School students integrate these values with their use in the digital era. This research method uses content analysis qualitative (qualitative analysis method). The data sources used are pledge texts, observation notes, and interviews with students of Islamic High School Al-Azhar 15 Semarang. The steps taken in this research include data preparation and collection, coding, data organization, analysis and interpretation, and report preparation. The results showed that the character values in the morning pledge text include the characters of faith, obedience, humility, and gratitude by being devoted to parents. These character values are in line with Islamic teachings and have high relevance in facing the challenges faced by students in the digital era.